Discovery of endogenous nitroxyl as a new redox player in Arabidopsis thaliana - Arasimowicz Jelonek, M. (2023)
Nitroxyl (HNO) is the one-electron reduced and protonated congener of nitric oxide (•NO), owning a distinct chemical profile. Based on real-time detection, we demonstrate that HNO is endogenously formed in Arabidopsis. Senescence and hypoxia induce shifts in the redox balance, triggering HNO decay or formation mediated by non-enzymatic •NO/HNO interconversion with cellular reductants. The stimuli-dependent HNO generation supports or competes with •NO signalling, depending on the local redox environment.